The Information Society: From Gutenberg to S.W.I.F.T. - Wriston, Walter B. (Tufts Archival Research Center, 2007)
The document was created from the speech, "The Information Society: From Gutenberg to S.W.I.F.T.," written by Walter B. Wriston for the S.W.I.F.T. Conference SIBOS '82 on 23 September 1982. The original speech is located in MS134.001.005.00004.